TRANFORMASI MADRASAH DI ERA DIGITAL: MEMBANGUN GENERASI EMAS: Madrasah Transformation in the Digital Era: Building the Golden Generation - Ibnu Ruslanil Fajri; Samsul Aripin (STAI Ma'had Aly Al-Hikam Malang, 2025)
Transforming madrasas in the digital era is no longer an option, but a necessity to build Indonesia's golden generation. The transformation of madrasas touches many things, from infrastructure, curriculum to teaching and education personnel. This article was prepared using qualitative methods and library research. The data source is literature relevant to the theme of the discussion. The findings of the article are: 1) The significance of madrasah transformation includes: Improving the quality of learning; Differentiated learning; Administrative efficiency; Relevant to the times; 2) The benefits of madrasah transformation are felt by students, teachers and education personnel, such as interactive and flexible learning; 3) Madrasah transformation strategies include: Infrastructure provision; Digital training; Digital curriculum; and Budget allocation; 4) The challenges of madrasah transformation include: Infrastructure limitation; Digital divide; Budget limitation and Resistance to change; 5) Solutions to the challenges of madrasah transformation are developing Partnerships, Innovation, Advocacy and Education. Transformasi madrasah di era digital bukan lagi pilihan, tetapi keharusan untuk membangun generasi emas Indonesia. Transformasi madrasah menyentuh banyak hal, mulai dari infrastruktur, kurikulum hingga tenaga pendidik dan kependidikan. Artikel ini disusun menggunakan metode kualitatif dan jenis penelitian pustaka. Sumber datanya adalah literatur yang relevan dengan tema bahasan. Temuan artikel adalah: 1) Signifikansi transformasi madrasah meliputi: Meningkatkan kualitas pembelajaran; Pembelajaran berdiferensiasi; Efisiensi administrasi; Relevan dengan perkembangan zaman; 2) Manfaat transformasi madrasah dirasakan oleh siswa, guru dan tenaga kependidikan, seperti pembelajaran yang interaktif dan fleksibel; 3) Strategi transformasi madrasah meliputi: Penyediaan infrastruktur; Pelatihan digital; Kurikulum digital; dan Pengalokasian Anggaran; 4) Tantangan transformasi madrasah antara lain: Keterbatasan infrastruktur; Kesenjangan digital; Keterbatasan anggaran dan Resistensi terhadap perubahan; 5) Solusi atas tantangan transformasi madrasah adalah mengembangkan Kemitraan, Inovasi, Advokasi dan Edukasi. Kata Kunci : Era Digital; Generasi Emas; Transformasi Madrasah.